The Effect of Complimentary Split Ring Resonator Placement on Antenna Patch and Ground Plane to Microstrip Antenna Reduction Dimension and Bandwidth - Habib Muharry Yusdartono; Fitri Apriyulida; Ananda Faridhatul Ulva (G-Tech: Jurnal Teknologi Terapan, 2025)
This reasearch is aimed to observe the comparison of CSRRs performance on Antenna Patch and Ground Plane so that the Antenna can be implemented in ADS-B frequency.  The CSRR outer dimension is 13 mm x 10 mm and  the inner dimension is 9 mm x 6 mm, obtained  of Return loss and VSWR simulation are respectively -13.7860 dan 1.5141. The iteration is done after the CSRR is added to its Patch and ground plane so that return losses  are -10,329 dB and -13,554 dB and the VSWRs  obtained were 1.8755 and 1.5317. In addition, the redution of Patch and Ground plane dimensions also is occurred when CSRR is on Patch by 18.5% and 30.2%, reduction Patch and Ground plane dimension occurred when CSRR is on Ground plane by 24.1% and 23.16%.  Etched on Patch and Ground plane, CSRRs effect Bandwidth, Bandwicth decreases at 0.015 GHz at CSRRs on patch and increases at 0.040 GHz whereas Bandwidth is 0025 GHz before CSRRs is etched.